Sky ranch : reared in the high country - Lockwood, Linda M. (She Writes Press, 2024)
"At the age of eight, Linda Lockwood moves with her family to an isolated ranch in eastern Washington State. Within two years, she's patrolling the ranch on horseback alongside her border collie ; herding sheep, killing rattlesnakes, and defending the ranch's livestock from coyotes, bears, and even trespassing hunters ; and working tirelessly to realize her dream of training horses. But her most daunting challenge is one hard work can't overcome: her mother is descending into madness. And Linda's deepest fear is that she might inherit the schizophrenia that threatens to dismantle her family. At age twenty-five, Linda marries, but the joy of her first pregnancy is darkened by her mother's suicide. Then she endures a painful miscarriage and the death of her beloved grandmother, traumatic events that send her back in time to the births and deaths of animals, domesticated and wild, that she loved in childhood. Eventually, her own family grows, but her happiness is haunted by questions people have tiptoed around all her life. How did her mother become schizophrenic? What did she endure as a patient in 1960s mental hospitals? Might Linda and even her children be next to battle that catastrophic mental disorder? Driven by the courage and will she sharpened as a rancher, Linda vows to find out"--